Application of PCR-Based DNA Fingerprinting Techniques for the Genetic Differentiation of Vibrio cholerae Non-01/Non-0139 Isolates from Kuching, Sarawak - Vincent, Mickey; Lai, Lee San; Ng, Lee Tze Ng; Apun, Kasing (Borneo Journal of Resource Science and Technology, 2016)
Fifty-four Vibrio cholerae non-01/non-0139 isolates were evaluated for their genetic diversity via randomly amplified polymorphic DNA-PCR (RAPD-PCR), enterobacterial repetitive intergenic consensus-PCR (ERIC-PCR) and BOX-PCR assays. Based on the various PCR fingerprints, the V. cholerae isolates were successfully differentiated into 39 types by RAPD-PCR, 43 types by ERIC-PCR, and 38 types by the BOX PCR, with the overall average polymorphic distances observed to be at 0.593, 0.527 and 0.504, respectively. The Simpson’s index of diversity of the isolates based on the fingerprinting analyses indicated that these DNA fingerprinting methods have high discriminatory power 0.986 (RAPD-PCR), 0.992 (ERIC-PCR) and 0.983 (BOX-PCR), and could be used independently or as supplements to other methods for the epidemiological investigation of the V. cholerae from water and seafood sources. The dendrograms constructed also showed that the V. cholerae isolates were clustered into several main clusters and sub-clusters, suggesting that different strains were circulating in the water environment and in the seafood sources. We conclude that molecular genotyping of V. cholerae isolates from surface water and seafood samples in Kuching, Sarawak (Malaysia) enabled high level observation of clonal diversity within V. cholerae isolates, and is directly applicable for the molecular epidemiological studies of the V. cholerae isolates.